2018
DOI: 10.11648/j.abb.20180602.12
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Isolation of <i>Escherichia coli</i> 0157:H7 from Diarrhoeic and Non-Diarrhoeic Children in Selected Communities in Cross River State, Nigeria

Abstract: Escherichia coli O157:H7 has been considered an emerging foodborne pathogen causing severe diarrheal disease globally especially among children under the age of five years in Sub-Saharan Africa. This study was aimed at conducting a comparative study on the rate of isolation of Escherichia coli O157:H7 from diarrhoeic and non-diarrhoeic children in selected communities in Cross River State, Nigeria. Stool samples were collected from children under the age of five yrs and the pathogen isolated and identified usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The detection of E. coli and S. aureus in the samples may be attributed to the fact that these pathogens are common contaminants in the hospital environment and are commonly found in the gastrointestinal tracts of both humans and animals. 3,5,21 Direct and indirect fecal contamination of wastewater from hospitals and healthcare centers is a common phenomenon, which may contribute to the development of antibiotic-resistant strains that can horizontally disseminate to other organisms. A similar study on untreated liquid hospital waste reported the highest resistance (75%) among E. coli isolates to amoxicillin, although its prevalence value of 24.1% was significantly lower than that obtained in this study.…”
Section: Antibiotic Resistance Of Escherichia Coli and Staphylococcus...mentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of E. coli and S. aureus in the samples may be attributed to the fact that these pathogens are common contaminants in the hospital environment and are commonly found in the gastrointestinal tracts of both humans and animals. 3,5,21 Direct and indirect fecal contamination of wastewater from hospitals and healthcare centers is a common phenomenon, which may contribute to the development of antibiotic-resistant strains that can horizontally disseminate to other organisms. A similar study on untreated liquid hospital waste reported the highest resistance (75%) among E. coli isolates to amoxicillin, although its prevalence value of 24.1% was significantly lower than that obtained in this study.…”
Section: Antibiotic Resistance Of Escherichia Coli and Staphylococcus...mentioning
confidence: 99%
“…E. coli O157:H7, an enterohaemorrhagic pathogen associated with human diarrhoea, can potentially be released into the healthcare environment through wastewater effluents. 3 Previous studies have reported an increase in the number of multidrug-resistant pathogens within the hospital environment due to the routine discharge of antibiotics into the environment, either in metabolized or unmetabolized forms. Microorganisms in hospital effluents tend to develop resistance to the antibiotics released alongside them in order to survive in such environments.…”
mentioning
confidence: 99%